21 Denuded descemet's membrane as potential tool to support human embryonic stem cell derived retinal pigment epithelial cells culture. (16th November 2022) - Daniele, Miss Elena; Bosio, Lorenzo; Ferrari, Stefano; Barbaro, Vanessa; Rassu, Nicolò; Ferrari, Barbara; Ponzin, Diego
Abstract : Introduction: Recent clinical studies suggest that RPE-cell replacement therapy may preserve vision and restore retinal structure in retinal degenerative diseases. New developments enabled the differentiation of RPE cells from pluripotent stem cells. Scaffold-based methods are being tested in ongoing clinical trials for delivering these cells to the back of the eye. Borrowed materials from donor tissues can be used as cell supports in subretinal transplantation. These biological matrices resemble the extracellular matrix microenvironment of the native tissue. The Descemet's membrane (DM) is an example of high collagen-rich basement membrane (BM). The potential of this tissue in retinal repair remains to be uncovered. Aims: To investigate human embryonic stem cell-retinal pigment epithelium (hESC-RPE) cells survival and behaviour on a decellularized DM, which may be of clinical relevance in retinal transplantation. Materials: DMs were isolated from human donor corneas and treated with thermolysin. The DM surface topology and the efficiency of the denudation method were evaluated by atomic force microscope and histology. hESC-RPE cells were seeded onto the endothelial-side surface of acellular DM in order to determine the potential of the membrane to support hESC-RPE cell culture, alongside maintaining their viability. Integrity of the hESC-RPE monolayer was assessed by measuring transepithelial resistance. RPE-specific gene, protein expression and growth factors secretion were assessed to confirm maturation and functionality of the cells over the new substrate. Results: Thermolysin treatment did not affect the integrity of the tissue, thus ensuring a reliable method to standardize the preparation of decellularized DM. hESC-RPE cell attachment 6 days post-seeding and proliferation rates over the acellular DM were similar to hESC-RPE cells cultured on tissue culture inserts. On the new matrix, hESC-RPE cells succeeded in forming an intact monolayer with mature tight junctions. The resulting cell graft showed the characteristic RPE morphology. The expression of typical RPE genes, proper protein localization and key growth factor secretion further confirmed the correct RPE phenotype. The viability of the cells was maintained for up to 4 weeks in culture. Conclusion: Acellular DM was shown to be capable of sustaining hESC-RPE cells growth, thus confirming to be potentially a valid alternative to the Bruch's membrane. Further in vivo studies will need to verify if this product can represent a feasible tool to deliver RPE cells in the back of the eye. Our study highlights the possibility of recycling unsuitable corneal tissues, which would otherwise be discarded by the eye banks for clinical application.